PENGARUH GAYA KEPEMIMPINAN, KOMPETENSI, DAN MOTIVASI PEGAWAI TERHADAP KUALITAS PELAYANAN PADA KANTOR PERTANAHAN KABUPATEN MUSI RAWAS - Gunadi Rusydi; Yohanes Susanto; Harni Harni (Jurnal Media Ekonomi (JURMEK), 2020)
The purpose of this study is to study leadership motivation, competence, and motivation for service quality in the Musi Rawas Land Office, both simultaneously and partially. The sample of this study were 50 employees at the Musi Rawas Land Office. The research data were collected with a questionnaire submitted through data quality tests namely validity and reliability and hypothesis testing using multiple linear regression, t test of determination (R2) and f test. Through testing the correlation coefficient (R) Obtained from the level of competition or the relationship between leadership style, competence, and work motivation of employees has a high relationship that is 94.6%. The result of determination (R2) of 89% means that the percentage of style motivation, employee competence and motivation towards service quality is 89% in this study. The results of the partial test (t test) and simultaneous test (f test) were carried out to prove the leadership style, competence and work motivation that were significant to the quality of service at the Musi Rawas Land Office. calculate which is higher than ftabel that is 389,472> 2.81 and the probability (sig 0,000) is less than or less than 0.05 So Ha; accepted and Ho; rejected. The most dominant variable affecting service quality at the Musi Rawas Land Office is competency with a conversion value of 0.944. A positive and strong relationship which means getting higher competence will be higher than the quality of service at the Musi Rawas Land Office.